Functional analysis of Drosophila melanogaster gene regulatory sequences by transgene coplacement. - Parsch, J. (Genetics, 2004)
The function of putative regulatory sequences identified by comparative genomics can be elucidated only through experimentation. Here the effectiveness of using heterologous gene constructs and transgene coplacement to characterize regulatory sequence function is demonstrated. This method shows that a sequence in the Adh 3'-untranslated region negatively regulates expression, independent of gene or chromosomal context.